Generational Patterns in Digital Linguistic Styles: A Quantitative Study of Millennials, Gen Z, and Gen Alpha - Maria Angela Macomis; Aviel I Alayon; Justine Mae Bihasa; Colleen Kate Pasion (Journal of Gender and Millennium Development Studies, 2026)
Background: The rapid evolution of digital technology has transformed communication and shaped linguistic practices across generations, yet localised empirical evidence remains limited. Objective: This study aims to examine how communication-related variables influence the digital language practices of Millennials, Generation Z, and Generation Alpha. Method: A quantitative descriptive-comparative and correlational design was employed, involving 75 respondents. Data were collected through a structured survey and analysed using descriptive statistics, one-way ANOVA, and Pearson correlation. Results: The findings revealed high levels of symbolic-paralinguistic use, alongside moderate levels of lexical innovation and multimodal integration. Significant generational differences were identified in lexical innovation and overall digital language practices, with Generation Alpha demonstrating higher levels. Furthermore, a moderate positive relationship was found between communication-related variables and digital language practices, with communication goals emerging as the strongest predictor, while digital literacy showed minimal influence. Conclusion: The study concludes that digital language practices are driven more by communicative intent and interaction patterns than by technical skills. Contribution: This research contributes to the fields of digital communication and linguistics by providing localised, cross-generational empirical evidence and highlighting the importance of social and functional factors in shaping evolving digital language use.